General Practice Nurse Conference 2019. (2nd July 2019) - Brown, Debbie
Abstract : The GPN Conference, organised by Practice Nursing Editor-in-ChiefDebbie Brown, hosted several speakers and discussed some of the most relevant issues facing the profession today, including leadership, sexual health and embracing Primary Care Networks